Anticancer activity of MDM2 inhibition in 2D and bioprinted 3D retinoblastoma cell models - Bompan, Francesca; Lodi, Giada; Foschi, Rebecca; Dipinto, Anna; Cosenza, Lucia Carmela; Casciano, Fabio; Severi, Paolo; Sanvido, Anna; Caruso, Lorenzo; Giari, Luisa; Zauli, Giorgio; Voltan, Rebecca; et al. (Frontiers in Pharmacology, 2025)
Retinoblastoma is the most common childhood tumor affecting the retina. Pharmacological resistance or delayed intervention leads to the loss of vision. Therefore, novel therapeutic strategies need to be assessed in preclinical models that mimic the in vivo tumor. This project aims to investigate the anticancer activity of the MDM2 inhibitor, nutlin-3a, in the treatment of retinoblastoma using both conventional 2D in vitro models and more-realistic 3D-bioprinted models. Unlike many cancers, retinoblastoma presents a p53 wild-type phenotype, making the p53 pathway a promising target for pharmacological treatment via MDM2 inhibitors. Initially, nutlin-3a was tested on Y79 and Weri-Rb1 retinoblastoma 2D cell line cultures. A significant, concentration-dependent reduction in cell viability was observed as early as 24 h, associated with cell cycle blockade in both S and G2/M phases, assessed through cytofluorimetric analysis. Activation of the p53 pathway was observed by Western blotting. Second, the same cell lines were used to generate innovative 3D-bioprinted models using 2% alginate and 5% gelatin bioinks. The 3D structures were treated with nutlin-3a for 72 h and assessed for viability using MTT or fixed and embedded in paraffin for histological and immunohistochemical investigation. Hematoxylin and eosin staining of non-treated 3D structures evidenced an architecture similar to the primary tumor rosette formation. Interestingly, nutlin-3a treatment significantly reduced the dimension of rosettes in both 3D models; additionally, it reduced the number of rosettes in the Y79 3D model. These data were supported by a significant reduction in proliferation and a decrease in Ki-67 expression. Our 3D models closely resemble retinoblastoma tumor tissue and can serve as a platform to assess innovative drugs or implement the promising results on the use of MDM2 inhibitors for retinoblastoma treatment.